Exogenous melatonin activates the antioxidant system and maintains postharvest organoleptic quality in Hami melon (Cucumis. melo var. inodorus Jacq.) - Wang, Yue; Guo, Minrui; Zhang, Weida; Gao, Yujie; Ma, Xiaoqin; Cheng, Shaobo; Chen, Guogang (Frontiers in Plant Science, 2023)
Hami melon is prone to postharvest perishing. Melatonin is a signaling molecule involved in a variety of physiological processes in fruit, and it improves fruit quality. We hypothesized that melatonin treatment would improve the storage quality of Hami melon by altering its respiration and reactive oxygen species (Graphical abstract). Our results indicated that optimal melatonin treatment (0.5 mmol L −1 ) effectively slowed the softening, weight loss, and respiratory rate of the Hami melon fruit. Furthermore, melatonin markedly improved the antioxidant capacity of the fruit and protected it from oxidative damage by decreasing its contents of superoxide anions, hydrogen peroxide, and malondialdehyde. Melatonin significantly enhanced the activities of superoxide dismutase, catalase, ascorbate peroxidase, and peroxidase. The total phenol, total flavonoids, and ascorbic acid contents were maintained by melatonin treatment. This treatment also repressed the activities of lipase, lipoxygenase, and phospholipase D, which are related to lipid metabolism. Thus, exogenous melatonin can maintain postharvest organoleptic quality of Hami melon fruit by increasing its antioxidant activity and inhibiting reactive oxygen species production.